Operational Analysis of Rooftop Solar Power Plant at SMK Negeri 3 Kupang - De Lellis, Rachel Angela; Likadja, Frans James; Galla, Wellem Fridz (Teknik Elektro Universitas Siliwangi, 2025)
The implementation of 25 kWp On-Grid Rooftop Solar Power Plant at SMK Negeri 3 Kupang is expected to provide a solution to the problem of dependence on conventional energy and reduce school operational costs. Therefore, it is important to conduct an analysis of the Rooftop Solar Power Plant system at SMK Negeri 3 Kupang, in order to optimize the use of renewable energy and reduce school electricity operational costs. This study aims to determine the performance of the Rooftop Solar Power Plant and the amount of savings that occur. The research method used is a descriptive method and direct measurement of the inverter, MDP, LVMDP to measure the current and voltage to obtain the output power of the Solar Power Plant, PLN and load. The results of the study showed that the operational performance of the Rooftop Solar Power Plant can be known through the efficiency of the Rooftop Solar Power Plant at SMK Negeri 3 Kupang which was obtained with a maximum value that occurred on Saturday of 86.96%. The measurement results showed that there were savings in power and bills at SMK Negeri 3 Kupang. With savings for 7 consecutive days of 84.87%; 91.60%; 35.98%; 58.73%; 57.74%; 25.15%; 84.04%.